Response of different potato genotypes to deficit irrigation in North-Western plains of India (Indian Journal of Arid Horticulture, 2025)
Field-based experimental trials were undertaken to assess the influence of water deficit stress on the tuber yield performance of nine distinct potato (Solanum tuberosum L.) genotypes. The genotypic set comprised officially released indigenous cultivars, advanced-stage breeding clones, and two standard control varieties. The experimental design incorporated two irrigation regimes: a fully irrigated control treatment (FI) representing optimal water supply, and two deficit irrigation treatments - alternate skip irrigation (DI) and complete cessation of irrigation during the tuber bulking phase (CS) - to simulate varying intensities of water stress. Among the genotypes evaluated under water-limited conditions, the cultivar ‘Kufri Gaurav’ exhibited the highest total tuber yield, followed sequentially by ‘Kufri Ganga’, ‘Kufri Thar-2’, and ‘Kufri Kiran’, indicating superior adaptive responses to water deficit stress.